Narrativas Interativas Gamificadas (NIGs) aplicadas aos processos de ensino e aprendizagem de matemática financeira - Costa, Juliana Evaristo (2024)
Over the last few decades, digital technologies have been gaining prominence in the educational context. In this context, the present study discusses the concept of Gamified Interactive Narratives (NIGs) to label materials in digital format that use game elements (e.g., narratives and mechanics) to propose a context for problem- solving. The current work reports the development of a NIG, called Mel’s Journey, comprising the contents of percentage, simple interest and compound interest. The research main goal is to analyze the potential of this NIG in learning basic concepts of financial mathematics with 20 high school sophomore students at a public school in the State of Ceará.This research uses elements of intervention and exploratory research and brings a qualitative-quantitative approach to the analysis of the data collected. For data collection, 3 instruments were used: a pre-test, the problem situations available in the NIG and the Technical Assessment Instrument - Usability. Results point to a better performance in the NIG when compared to the pre-test, considering that the average score was 9.10 out of a total of 15 questions (60.7% correct) while in the pre-test, the average was 4.25 out of a total of 9 questions (47.2% correct). The usability test indicates a good acceptance of the NIG “Mel’s Journey” by students. Thus, the work indicates that the NIG enables better learning through the contextualization of present problem situations, narrative and game elements (gamification).